USING GAMIFICATION TO DEVELOP ENGLISH VOCABULARY LEARNING ABILITY FOR MATHAYOMSUKSA 1 STUDENTS - Chenparamakit, Wijitkhae; Moosikajaroen, Wiparat; Chimroylarp, Nopphawan (Journal of Educational Review Faculty of Education in MCU, 2024)
The purposes of this research were to: 1) develop English vocabulary learning ability for Mathayomsuksa 1 students by using gamification and 2) study Mathayomsuksa 1 students’ satisfaction towards English vocabulary learning by using gamification. This research was an quasi-experimental research based on one-group pretest-posttest design. The research instruments were: 1) lesson plans of English vocabulary learning by using gamification 2) the pre-test and post-test for English vocabulary 3) a satisfaction questionnaire towards English vocabulary learning by using gamification. The statistics used to analyze the data were mean, standard deviation (S.D.) and t-test for dependent samples. The research results were: 1) The students’ English vocabulary learning ability by using gamification were significantly higher than before at the .05 level. 2) The students’ satisfaction towards English vocabulary learning by using gamification were at high level.